FRI0222 Polymyalgia rheumatica and giant cell arteritis reveal a similar pattern at PET-CT. (23rd January 2014) - Camellino, D.; Morbelli, S.; Paparo, F.; Cutolo, M.; Sambuceti, G.; Cimmino, M.A.
Abstract : Background: Polymyalgia rheumatica (PMR) and giant cell arteritis (GCA) are two frequent overlapping diseases. The purpose of this work is to examine the relationship between these conditions by analysis of CT/PET findings. Methods: Fourty consecutive, untreated patients (30 PMR, 10 GCA, of whom 6 also had PMR) and 40 age-matched controls with suspected neoplastic disease, but without autoimmune disease or previous chemiotherapy, radiotheraphy, and glucocorticoid treatment, were studied. They underwent simultaneous FDG-PET and CT imaging from the skull base to the knee using an integrated PET/CT scanner (Hirez; Siemens Medical Solutions, Knoxville TN, USA). Arterial and joint metabolism were calculated drawing regions of interest (ROIs) on thoracic and abdominal aorta, subclavian, common carotid, iliac and femoral arteries, on gleno-humeral, sternoclavicular, coxo-femural joints, and on trochanteric, and ischiatic bursae. Intergroup differences in arterial SUV were tested in each vascular and joint segment using the Kruskal-Wallis test (MedCalc, Belgium). Results: Among the studied arteries, an increased uptake was seen only in the carotid arteries (see table ) (p=0.04) in PMR patients vs. controls. The shoulder and sternoclavicular joints, and the trochanteric and ischiatic bursae were more commonly affected in patients than in controls. PMR patients showed an increased uptake in the shoulders also in comparison with GCA patients (p<0.0001). In coxofemoral joints the uptake of patients and controls was similar. When all articular districts were considered together (mean joint uptake), there was significant difference between patients and controls (p<0.0001). Conclusions: With the limitation of the small number of GCA patients included and of the absence of histological data on the temporal arteries of PMR patients, our study confirms that PMR and GCA could be different forms of the same condition. In particular, large arteries inflammation was very similar, and not dissimilar from age-matched controls, except for the carotid arteries. Joint involvement was significantly more pronounced in PMR and GCA than in controls, except for the pelvic girdle. PET/CT, a minimally invasive technique, is an effective and objective method to evaluate inflammation in PMR/GCA. Disclosure of Interest: None Declared